Annual reports on NMR spectroscopy. Volume 56 - Webb, G. A. (Graham Alan), 1935-; ScienceDirect eBooks (Amsterdam ; Boston : Elsevier Academic Press, 2005)
Nuclear magnetic resonance (NMR) is an analytical tool used by chemists and physicists, to study the structure and dynamics of molecules. It is used in branches where structural determination is required. This book aims to act a means for the specialist and nonspecialist, to become familiar with the techniques and applications of NMR spectroscopy.
Cover; Annual Reports on NMR Spectroscopy; List of Contributors; Contents; Small-Volume and High-Sensitivity NMR Probes; Continuous-Wave NMR Imaging in the Solid State; Solution- and Solid-State NMR Studies of Eight- and Nine-Membered Medium Ring Cis-Cycloalkene Stereochemistry; Methods and Applications of Quantitative MRI; Secondary Relaxation Processes in Molecular Glasses Studied by Nuclear Magnetic Resonance Spectroscopy; Index.
Includes bibliographical references and index.
Print version record.
Elsevier
Keywords: Nuclear magnetic resonance spectroscopy; SCIENCE -- Physics -- Magnetism; Nuclear magnetic resonance spectroscopy; Electronic books